Building method of distributed COW disk on network computing environment - Huai-liang TAN; Zheng LUO; Zai-hong HE; Ren-fa LI (Tongxin xuebao)
Aiming to distributed computing and data centralizing storage in large-scale network computing environments and combining sparse and bursting characteristic of COW(copy-on-write) disk storing modified data blocks,the distributed COW network disk architecture was presented.The system building process of network computing environments was speeded up by apportioning the aggregation spending that server manages all related COW disks of client hosts to each client host.A improving 64bit bitmap compress arithmetic was designed to reduce the size of COW disk’s bitmap,so server disk space was saved and the network communication spending of distributed COW disk was less.The modified prefetching arithmetic based on COW bursting blocks was presented to improve the hit rate of Cache relating with distributed COW disk.Experiments on the prototype show that the distributed COW mechanism can effectively reduce system building latency of multi-client hosts network computing environment based on improving COW bitmap compress and prefetching arithmetic.